Reform of The Intergovernmental Transfer System In China - Shah, Anwar, 1948- 1948- (The World Bank, 2007)
In China, most of the service delivery responsibilities are assigned to the subnational governments. Yet for reasons of efficiency in tax collection and administration, the central government collects revenues far in excess of its expenditure needs. In 2003 the central government collected 70 percent of consolidated revenues but accounted for only 30 percent of consolidated expenditures. The initial fiscal surplus of the central government enables it to use its spending power to provide financing to subnational jurisdictions for the achievement of national objectives and to influence local priorities. This paper examines the incentives associated with the design of such transfers and their implications for the efficiency and equity of public service provision and accountable local governance in China. The paper argues that the existing design of such transfers is not consistent with efficiency and equity considerations. It further undermines local autonomy without enhancing local accountability while creating incentives for imprudent fiscal management. Its main limitations include a complex and opaque system, a piecemeal approach to gap filling, lack of consistency of design with objectives, focus on input controls without regard for output accountability, incentives to support an antiquated management paradigm, a one-size-fits-all approach to local financing, and lack of transparency and regulatory framework for the intergovernmental transfer system. The paper makes specific suggestions on a reform of this system to overcome these limitations and on better use of fiscal transfers to create responsive, responsible, equitable, and accountable local governance in China